O clipping como fonte de informação para inteligência competitiva : uma proposta para a UFSCar - Arato, Agnes Dias (2018)
The advent of the Knowledge Society has brought new challenges to the management of organizations. The speed of events and the abundance of information resulted in the need to monitor the environment and to remain flexible and open to constant changes, which requires that organizations, as well as people, are constantly learning, evaluating experiences, collecting hints and data and turning them into knowledge. Within this context, organizations need to re-evaluate traditional processes, often performed without reflection, so that they can provide this learning possibility. In light of this, by using the concepts of Competitive Intelligence and Bibliometrics, this paper proposes the elaboration of indicators for the monitoring of the institutional image and the relationship of the Federal University of São Carlos (UFSCar) with the press. The research method used was the case study and bibliometrics was the technique of information analysis applied to the analyzed sample, which comprised 3,823 bibliographical records collected by the clipping service and performed by the Coordination of Social Communication (CCS) of UFSCar (case unit). The results obtained were: 1] a set of bibliometric indicators on institutional image and relationship with the press; and 2] the diagnosis of the clipping process, in order to reformulate it. It was concluded that the indicators and the diagnosis contribute to the generation of intelligence for the decision-making process, based on data and information already collected on a regular basis by the clipping process.